RANCANG BANGUN APLIKASI RUMUS ELEKTRONIKA BERBASIS ANDROID MOBILE (Information Technology and Telematics, 2013)
Along with the rapid development of technology today, media communication and information more widely provide convenience for interacting between users. In this case, the phone is one form of technological development that are not only useful as a communication tool, but also as a medium of entertainment and learning. This fact can be proven with the development of various types of smartphones that were made leading handset vendors in the world. It is either directly or indirectly affect the development of education in Indonesia in developing a wide range of technologies. Electronics is the science that studies the control of electric current that can be operated by means of controlling the flow of electrons. Knowledge of basic electronics learning process needs to be optimized so that the students and the general public have a strong understanding and knowledge of the fundamental.With the development of mobile devices in Indonesia is more advanced and the large variety of mobile platforms that allow developers to design applications or software that is used for learning and information delivery media. Through the medium of mobile applications in the world of education this would be a breakthrough to enhance effectiveness in the learning process.The purpose of this final report is design a mobile application that can be used as a medium of learning formulas electronics. And aims to increase interest in learning for users to take advantage of Android-based mobile media.Keywords : Design Build, Electrical Formulas Application, Android-Based Mobile